TUMBLR META-FANDOM: REFLECTIONS AND REPAIR - Neill Hoch, Indira (AoIR Selected Papers of Internet Research, 2023)
Drawing from qualitative interviews with nine active Tumblr users conducted in the Fall/Winter of 2021-2022 and qualitative multimodal analysis of high-circulation “popular” Tumblr posts, this research assesses and analyzes transformations in user attitudes towards Tumblr three years on from Verizon’s porn ban, and immediately prior to and following additional attempts to restrict adult content enacted by Automattic. This research considers iterations of Tumblr’s meta-fandom, or fan practices centered around Tumblr’s cultures and communities themselves, rather than a more traditional media property (Tiidenberg, Hendry, & Abidin, 2021), as locations where nostalgia and repair are contested. Meta-fandom practices are analyzed through the lenses of reflective nostalgia (Boym, 2001) and repair (Jackson, 2014) as a way of contending with both the recounting of a place and time on Tumblr that the users themselves know never really existed and the desire to acknowledge that Tumblr always has been “broken” but users continue to thrive, even in the wake of declining overall usage.